Faktor-Faktor yang Mempengaruhi Penggunaan Sistem Informasi Akuntansi pada UMKM di Kabupaten Sidoarjo - Salsabila Asadawa Tasya; Yanthi, Merlyana Dwinda (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a crucial role in supporting the economy in Indonesia. Therefore, MSMEs need to enhance their competitiveness through the use of accounting information systems. The use of accounting information systems generates reliable business information, leading to better business decision-making. This study aims to identify the factors that influence the use of accounting information systems in MSMEs, which include educational background, availability of technological facilities, business scale, and accounting training. The subjects of this study are the owners/managers of MSMEs operating in Sidoarjo Regency. The data used in this research is primary data obtained from questionnaires distributed to respondents. The sample used in this study consists of 97 respondents. The data analysis techniques employed include descriptive statistics, validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, and hypothesis tests using SPSS 25. The results show that educational background, availability of technological facilities, business scale, and accounting training positively influence the use of accounting information systems in MSMEs in Sidoarjo Regency.